Novel cobalt-based carbon bead material and preparation method thereof
Through the design of cobalt-based carbon bead material, the combination of polyacrylonitrile and ZIF-67 and graphene oxide doping are used to form a carbon bead structure rich in active sites, which solves the problems of low activation efficiency and difficulty in recycling of existing catalysts, and achieves efficient removal of organic pollutants and maintains good recycling.
Patent Information
- Application Number
- CN202411721018.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
The existing metal catalysts have low activation efficiency when activating persulfate, their degradation effect is not ideal, and nanomaterials are difficult to recycle, which limits their engineering applications.
Cobalt-based carbon bead material is used to form a carbon bead structure rich in active sites through the combination of polyacrylonitrile and ZIF-67 and the doping of graphene oxide, which improves catalytic efficiency and facilitates recycling through spherical morphology.
The antibiotic sulfamethoxazole was efficiently removed under the lower material dosage and persulfate dosage. The catalyst still maintained a removal rate of 82.4% after multiple recycles, and the spherical morphology was conducive to recovery.
Smart Images

Figure HSA0000299844010000011 
Figure HSA0000299844010000012 
Figure HSA0000299844010000021
Abstract
Description
Technical Field
[0001] This patent belongs to the field of environmental pollution control technology, and specifically relates to a new cobalt-based carbon bead material and its preparation method for activating persulfate and oxidatively degrading environmental organic pollutants. Background Art
[0002] Advanced oxidation process is currently the most common and effective method for treating antibiotic pollutants in water. Metal-based catalysts can effectively activate persulfate to produce free radicals (sulfate radicals, hydroxyl radicals and superoxide radicals) and non-free radicals (singlet oxygen). Many studies have shown that superoxide radicals cannot directly degrade pollutants, but can only indirectly mediate the production of sulfate radicals, hydroxyl radicals and singlet oxygen and other free radicals or non-free radicals that can be effectively degraded; however, this method has a low activation efficiency and the degradation effect is not ideal. In conventional metal catalysts, there is usually saturation of active sites, which limits the further improvement of the degradation rate. Therefore, the introduction of a variety of active sites and the effective use of superoxide radicals can achieve the purpose of further stimulating the catalytic performance of the material.
[0003] Metal ions such as cobalt, copper, and manganese are considered to be effective homogeneous metal catalysts for activating persulfate, among which cobalt ions have the best effect. Cobalt single atoms, cobalt-based nanocatalytic materials, etc., have attracted much attention because they can expose more active sites and obtain higher catalytic efficiency. However, in practical applications, how to achieve efficient recycling is a more realistic issue. Nanomaterials are not only prone to agglomeration, but also prone to metal leaching, and are not conducive to recycling, which greatly limits their engineering applications. Therefore, it is of great significance to develop catalytic materials with higher catalytic efficiency and recyclability. The commonly used method is to load nanomaterials onto macroscopic carriers, but the problem of metal ion leaching has not been effectively solved, and the volume of block structure materials is relatively large, which has the problem of limited application scenarios. At the same time, due to the limitations of active sites, the catalytic effect is not ideal. Summary of the invention
[0004] In order to increase the service life of the active sites of metal catalysts and solve the problems of poor metal leaching and recycling, the present invention provides a preparation method and application of a cobalt-based carbon bead catalyst.
[0005] The mechanism of action of the present invention is as follows (taking preferred polyacrylonitrile and dimethylimidazole cobalt (ZIF-67) as examples:
[0006] Polyacrylonitrile is insoluble in water but soluble in organic solvents. After being evenly mixed with ZIF-67, the mixed solution is dripped into water to solidify; the outside of the polyacrylonitrile forms beads, and the inside forms a supporting skeleton with evenly distributed ZIF-67 nanoparticles. In addition, polyacrylonitrile is doped with graphene oxide. After calcination in a nitrogen atmosphere, more pores appear inside the carbon beads. The metal cobalt near the shell in the beads forms elemental cobalt due to the escape of oxygen atoms, and the metal cobalt ions inside form cobalt tetroxide through the oxygen atoms provided by graphene oxide. This specific structure enriches the active sites of the material and can efficiently activate persulfate; and the beaded morphology is conducive to recycling and reuse.
[0007] The present invention is achieved in that:
[0008] (1) Dissolve ZIF-67 in N,N-dimethylformamide solution and perform ultrasonic treatment for 1 h to obtain a purple viscous liquid;
[0009] (2) dissolving graphene oxide and polyacrylonitrile in N,N-dimethylformamide solution respectively and stirring in a water bath at 60° C. for 1 h to obtain a brown viscous liquid;
[0010] (3) Slowly add the purple liquid obtained in step (1) into the brown liquid in step (2) and continue stirring in a water bath for 3 h;
[0011] (4) slowly adding the mixed liquid obtained in step (3) into pure water using a needle syringe to obtain purple beads;
[0012] (5) The purple beads obtained in step (4) are washed with pure water several times and then dried. They are then placed in a tubular furnace and calcined at 800°C for 4 h at a heating rate of 5°C / min. After natural cooling, black carbon beads with a diameter of 1.0-3.0 mm are obtained.
[0013] The preparation method of ZIF-67 in step (1) is as follows: Co(NO3)2·6H2O is dissolved in purified water, ultrasonically treated to ensure uniform dispersion, and recorded as solution A; 2-methylimidazole is dissolved in purified water, triethylamine is added and ultrasonically treated, and recorded as solution B; A is slowly added to solution B at room temperature, and after magnetic stirring, the precipitate is washed with clean water, centrifuged, repeated several times, and finally dried to obtain purple powder ZIF-67.
[0014] The invention also provides application of the cobalt-based carbon bead catalyst prepared by the preparation method in activating persulfate to remove organic pollutants.
[0015] Further:
[0016] The organic pollutant is the antibiotic sulfamethoxazole.
[0017] The amount of the obtained cobalt-based carbon bead catalyst was 0.1 g / L. Under the condition of 0.1 g / L persulfate, the degradation reaction was carried out with 10 mg / L sulfamethoxazole (SMX). After 15 minutes of reaction, a removal rate of 100% could be achieved.
[0018] The advantages of the present invention are:
[0019] (1) The liquid-liquid phase conversion method is used to form the material into millimeter-scale spheres. Unlike traditional micro-nano powder catalysts, spherical materials are more conducive to recycling and reuse and can be applied in a variety of scenarios. In addition, metal nanoparticles are encapsulated in spheres, which effectively retains the catalytic performance while minimizing metal leaching.
[0020] (2) The metal cobalt-based carbon bead material provided by the present invention can achieve a 100% sulfamethoxazole removal rate within 15 minutes under the conditions of low material dosage and persulfate dosage. The cobalt-based carbon bead catalyst maintains its own macroscopic structure while showing a catalytic effect comparable to that of other traditional powder catalysts.
[0021] (3) The metal cobalt-based carbon spheres provided by the present invention degrade pollutants through free radical pathways (sulfate radicals, hydroxyl radicals) and non-free radical pathways (singlet oxygen, electron transfer), while efficiently utilizing superoxide radicals to accelerate degradation. They can effectively resist the influence of multiple factors such as different pH values, inorganic salts and natural organic matter in the reaction system, and can still maintain a good effect of removing target pollutants in a complex pollution system.
[0022] (4) The metal cobalt-based carbon bead material provided by the present invention can still maintain a removal rate of 82.4% after being used in four cycles, showing good recyclability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The diagram shows the effects of activated persulfate on degradation of sulfamethoxazole in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1.
[0024] Figure 2 The effect diagram of degradation of sulfamethoxazole by activated persulfate in Comparative Example 4, Comparative Example 5, Comparative Example 6 and Example 1 is shown.
[0025] Figure 3 a in the figure is a scanning electron microscope image of the interior of the material in the following comparative example 1.
[0026] Figure 3 b is a scanning electron microscope image of the interior of the material in the following comparative example 2.
[0027] Figure 3 c in the figure is a scanning electron microscope image of the interior of the material in the following comparative example 3.
[0028] Figure 3 d in the figure is a scanning electron microscope image of the interior of the cobalt-based carbon bead of the present invention.
[0029] Figure 4 This is the Raman spectrum of Example 1 after maintaining the original morphology and being ground into powder.
[0030] Figure 5 This is the reaction kinetic analysis of the degradation of sulfamethoxazole by activated persulfate in Example 1.
[0031] Figure 6 This is a diagram showing the effect of activating persulfate to degrade sulfamethoxazole under different anion conditions in Example 1.
[0032] Figure 7 This is a diagram showing the effect of activating persulfate to degrade sulfamethoxazole under different pH conditions in Example 1.
[0033] Figure 8 This is a diagram showing the effect of multiple cycles of activation of persulfate to degrade sulfamethoxazole in Example 1. DETAILED DESCRIPTION
[0034] The following embodiments are provided to facilitate a better understanding of the present application, but are not intended to limit the present application.
[0035] Example 1
[0036] A method for preparing a cobalt-based carbon bead catalyst, the specific steps of which are:
[0037] (1) Add 0.6 g ZIF-67 powder into 6 ml N,N-dimethylformamide solution and sonicate for 1 h.
[0038] (2) 0.6 g of polyacrylonitrile and 0.05 g of graphene oxide were added to 6 ml of N,N-dimethylformamide solution and stirred in a 60 °C water bath for 1 h to ensure that the polyacrylonitrile was completely dissolved.
[0039] (3) Slowly introduce the purple solution obtained in step (1) into step (2) and continue stirring in a water bath for 3 h.
[0040] (4) Using a 32G needle, slowly drip the liquid obtained in step (3) into pure water. The droplets solidify and are collected and dried to obtain purple spheres.
[0041] (5) The purple beads were placed in a tubular furnace and calcined in a nitrogen atmosphere at a heating rate of 5 °C / min and maintained at 800 °C for 4 h. Black beads were obtained after natural cooling.
[0042] (6) The black beads obtained in step (5) were washed with pure water several times and then dried to obtain the final product CoNC@cPAN / rGO-800.
[0043] Comparative Example 1
[0044] A method for preparing nitrogen-doped non-metallic carbon spheres, the steps of which are as follows:
[0045] (1) Dissolve 0.6 g of polyacrylonitrile in 6 ml of N,N-dimethylformamide solution in a 60°C water bath and stir for 4 h to ensure that the polyacrylonitrile is completely dissolved.
[0046] (2) Using a 32G needle, slowly drip the liquid obtained in step (1) into pure water. The droplets solidify and are collected and dried to obtain white spheres.
[0047] (3) The obtained white pellets were placed in a tubular furnace, calcined in a nitrogen atmosphere at a heating rate of 5°C / min, maintained at 800°C for 4 h, and black beads were obtained after natural cooling.
[0048] (4) The black beads obtained in step (3) are washed with pure water several times and then dried to obtain the final product cPAN.
[0049] Comparative Example 2
[0050] (1) Add 0.6 g polyacrylonitrile and 0.05 g graphene oxide to 6 ml N,N-dimethylformamide solution and stir in a 60 °C water bath for 1 h to ensure complete dissolution.
[0051] (2) Using a 32G needle, slowly drip the liquid obtained in step (1) into pure water. The droplets solidify and are collected and dried to obtain light yellow spheres.
[0052] (3) The obtained light yellow balls were placed in a tubular furnace, calcined in a nitrogen atmosphere at a heating rate of 5°C / min, maintained at 800°C for 4 h, and black beads were obtained after natural cooling.
[0053] (4) The black beads obtained in step (3) were washed with pure water for several times and then dried to obtain the final product cPAN / rGO.
[0054] Comparative Example 3
[0055] (1) Add 0.6 g ZIF-67 powder into 6 ml N,N-dimethylformamide solution and sonicate for 1 h.
[0056] (2) Add 0.6 g of polyacrylonitrile to 6 ml of N,N-dimethylformamide solution and stir in a 60°C water bath for 1 h to ensure that the polyacrylonitrile is completely dissolved.
[0057] (3) Slowly introduce the purple solution obtained in step (1) into step (2) and continue stirring in a water bath for 3 h.
[0058] (4) Using a 32G needle, slowly drip the liquid obtained in step (3) into pure water. The droplets solidify and are collected and dried to obtain purple spheres.
[0059] (5) The purple beads were placed in a tubular furnace and calcined in a nitrogen atmosphere at a heating rate of 5 °C / min and maintained at 800 °C for 4 h. Black beads were obtained after natural cooling.
[0060] (6) The black beads obtained in step (5) were washed with pure water several times and then dried to obtain the final product CoNC@cPAN.
[0061] Comparative Example 4
[0062] The material preparation process is consistent with that in Example 1, and the calcination temperature is 600°C.
[0063] Comparative Example 5
[0064] The material preparation process is consistent with that in Example 1, and the calcination temperature is 700°C.
[0065] Comparative Example 6
[0066] The material preparation process is consistent with that in Example 1, and the calcination temperature is 900°C.
[0067] Test Example 2: Catalytic degradation of sulfamethoxazole
[0068] The catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Comparative Example 6 were used to degrade sulfamethoxazole. The specific experimental method is as follows:
[0069] (1) Add 100 mL of 10 mg / L sulfamethoxazole solution to seven 250 mL beakers, place in a water bath shaker, set the temperature to 25 °C, and the speed to 40 rpm.
[0070] (2) 10 mg of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Comparative Example 6 were respectively weighed and added to the solution of (1).
[0071] (3) Add 1 ml of 10 mg / mL persulfate solution to the solution in step (2).
[0072] (4) Sampling was performed at 1 min, 3 min, 5 min, 7 min, 10 min, 15 min, 20 min, 25 min, and 30 min after the reaction. After sampling, 0.5 ml of the sample was taken through a 0.22 μm PTFE membrane and 0.5 ml of methanol was added for quenching. The absorbance at 257 nm was measured by high performance liquid chromatography to analyze the concentration. The results are shown in FIG. Figure 1As shown, Example 1 has the best catalytic degradation effect, and can complete the degradation of sulfamethoxazole within 15 minutes. This shows that the cobalt metal node brought by doping ZIF-67 is the key to improving the activation performance of the material, while simple graphene oxide doping cannot improve the degradation effect. Only when it is combined with cobalt metal can the corresponding acceleration effect be achieved. Figure 2 The degradation effects of Comparative Example 4, Comparative Example 5, Comparative Example 6 and Example 1 after calcination at different temperatures are shown. It can be seen that 800° C. is the optimal calcination temperature for the material.
[0073] Test Example 3: Surface morphology characterization
[0074] cPAN( Figure 3 a) with cPAN / rGO ( Figure 3 b) shows that the doping of graphene oxide makes the PAN skeleton produce more macropores after calcination. Figure 3 c) It can be clearly seen that many micropores are generated on the surface of the cPAN skeleton, indicating that ZIF-67 is effectively loaded on PAN, causing the nanotubes of ZIF-67 to shrink internally during the calcination process, and then hollow micropores are uniformly formed in the cPAN skeleton. Compared with CoNC@cPAN, GO-doped CoNC@cPAN / rGO-800 ( Figure 3 d) The above-mentioned characteristics of CoNC@cPAN are retained. The macroscopic pores in the carbon spheres are honeycomb-shaped, while the pores of CoNC@cPAN are more slender, indicating that graphene oxide plays an important role in modifying the carbon sphere skeleton.
[0075] Test Example 4: Material Dimension Measurement
[0076] By using a vernier caliper to measure the outer diameter of the CoNC@cPAN / rGO-800 sphere, ten samples were randomly selected, and the final size of CoNC@cPAN / rGO-800 was determined to be 1.32±0.36mm.
[0077] Test Example 5: Raman Test
[0078] In order to test the distribution of cobalt tetroxide in Example 1, CoNC@cPAN / rGO-800 was tested and compared in the original carbon bead form and the crushed powder form. Figure 4 It can be seen that the characteristic peak of cobalt tetroxide appears in the powder form of CoNC@cPAN / rGO-800, while cobalt tetroxide is almost unobservable in the CoNC@cPAN / rGO-800 that maintains a beaded form, indicating that cobalt tetroxide exists in the core part of Example 1, rather than near the shell part.
[0079] Test Example 6: Analysis of degradation kinetics
[0080] The degradation process of sulfamethoxazole by adding persulfate to CoNC@cPAN / rGO-800 was analyzed kinetically. Figure 5 It can be clearly seen that the degradation process is divided into two stages, the first stage of 0-3min and the second stage of 3-15min. By analyzing the degradation rate through the secondary reaction kinetic equation, it can be seen that the k value of the second stage is 0.2992, which is much larger than 0.0717 of the first stage. This shows that the internal cobalt tetroxide plays a key accelerating role in the second stage.
[0081] Test Example 7: Degradation effect under different anion conditions
[0082] In order to test the anti-interference ability of the catalyst in a complex environment system, Cl - 、NO3 - 、HPO4 2- , O4 2- , the concentration was 10mmol / L, and the rest of the experimental steps were the same as in Example 1. Figure 6 It can be seen that under anionic conditions, 100% removal rate can be achieved within 25 minutes.
[0083] Test Example 8: Degradation effect under different pH conditions
[0084] Depend on Figure 7 It can be seen that when the pH is 3, 5, 7, 9 and 11, sulfamethoxazole can be completely degraded within 30 minutes, which indicates that the catalyst can treat pollutants in a relatively wide pH range.
[0085] Test Example 9: Degradation Effect of Multiple Cycles
[0086] In order to test the recycling performance of the catalyst, after each use of the catalyst, the material was washed three times with pure water and then dried before continued use. Figure 8 It shows that after four cycles, the degradation efficiency can still reach 82.4%, reflecting good recycling performance.
[0087] Although the present application has been disclosed above through the description of the specific embodiments of the present application, it should be understood that those skilled in the art can design various modifications, improvements or equivalents to the present application within the spirit and scope of the attached scheme. These modifications, improvements or equivalents should also be considered to be included in the scope of protection claimed in the present application.
Claims
1. A new type of cobalt-based carbon bead material, characterized in that: A carbon bead material with a spherical multi-level ordered pore structure and the coexistence of polymorphic cobalt metals can efficiently activate persulfate in water and oxidatively degrade organic pollutants.
2. A novel cobalt-based carbon bead material according to claim 1, characterized in that: The carbon bead material is formed by co-calcining a high molecular polymer doped with graphene oxide and a metal organic framework structure material.
3. The high molecular polymer according to claim 2, including but not limited to polyacrylonitrile, polyimide, meta-aramid or polyethylene that can undergo liquid-liquid phase transition, preferably, the high molecular polymer is polyacrylonitrile.
4. The metal organic framework structural material according to claim 2, including but not limited to dimethyl imidazole cobalt, iron terephthalate, 1,3,5-pyromellitic acid copper, dihydroxy terephthalate manganese, etc. Preferably, the metal organic framework structural material is dimethyl imidazole cobalt.
5. A novel cobalt-based carbon bead material according to claim 1, characterized in that: The multi-level ordered pore structure includes abundant micropore (0.5-1.5 nm) and mesopore (5-20 nm) structures.
6. The multi-level ordered pore structure according to claim 5, characterized in that: The skeleton structure of the carbon bead material is orderly composed of cage-like mesopores and sponge-like micropores.
7. A method for preparing a novel cobalt-based carbon bead material, characterized in that: The preparation method and steps include: (1) dissolving the metal organic framework structure material in N,N-dimethylformamide solution and subjecting to ultrasonic treatment for 1 h to obtain a purple viscous liquid; (2) dissolving graphene oxide and high molecular weight polymer in N,N-dimethylformamide solution respectively and stirring in a water bath at 60° C. for 1 h to obtain a brown viscous liquid; (3) Slowly add the purple liquid obtained in step (1) into the brown liquid in step (2) and continue stirring in a water bath for 3 h; (4) slowly adding the mixed liquid obtained in step (3) into pure water using a needle syringe to obtain purple beads; (5) The purple beads obtained in step (4) are washed with pure water several times and then dried. They are then placed in a tubular furnace and calcined at 800°C for 4 h at a heating rate of 5°C / min. After natural cooling, black carbon beads with a diameter of 1.0-3.0 mm are obtained.
8. The novel cobalt-based carbon bead material according to claim 1, characterized in that: The material has a wide pH applicable range (3-11). In complex environmental conditions where multiple anions coexist, it can efficiently activate persulfate in water within 25 minutes and achieve complete degradation of the organic pollutant sulfamethoxazole.
9. The novel cobalt-based carbon bead material according to claim 1, characterized in that: As an environmentally friendly and recyclable catalyst, it breaks through the bottleneck of traditional macroscopic bead catalysts with poor catalytic effect, single reaction active sites and low electron utilization. It can maintain stable catalytic performance during multiple cycles, showing the advantages of high efficiency and sustainable catalysis.